Thyroid V40 as a potential early predictor of hypothyroidism following hypofractionated locoregional breast radiotherapy - Moemen Khalifa; Maher Soliman; Abbas Omar; Mohamed Abouegylah; Amr Munir Ameen; Yomna Mahmoud Mohamad; Waleed Arafat (PLoS ONE, 2026)
Radiotherapy (RT) is used quite often among breast cancer patients, and because these patients now live longer than they used to, long-term treatment-related adverse effects, such as hypothyroidism, are becoming increasingly relevant. Radiation-induced hypothyroidism is a late side effect of radiation to the thyroid gland, which could develop months to years after radiotherapy. However, there are insufficient data on hypothyroidism in patients with breast cancer who receive locoregional RT, which usually affects a portion of the thyroid gland. In this prospective study, we aimed to evaluate the association between radiation dose to the thyroid gland and early thyroid dysfunction in breast cancer patients treated with hypofractionated locoregional radiotherapy, and to establish potential planning objectives that could help in sparing the thyroid gland. Our study included 109 women who received 3-D conformal locoregional breast radiotherapy. These patients had normal thyroid function prior to start of radiotherapy. Patients had follow-up thyroid function tests 6 months after finishing radiotherapy. Based on dose volume histograms (DVH), the percentages of the thyroid volume, and ipsilateral thyroid lobe, receiving 5, 10, 15, 20, 25, 30, 35, and 40 Gy (V5, V10, V15, V20, V25, V30, V35, and V40 respectively), in addition to the mean and maximum thyroid doses, were estimated. Follow-up assessment of thyroid function and statistical analysis unveiled incidence of radiotherapy induced hypothyroidism to be 8.3%. Possible risk factors included high maximum radiation dose and V40 to the thyroid gland and the ipsilateral thyroid lobe, as well as high mean dose and smaller volume of the ipsilateral thyroid lobe. The likelihood of hypothyroidism was significantly increased with V40 of >5% of the thyroid gland, and V40 of >11% of the ipsilateral thyroid lobe. Further study is recommended for larger populations and longer follow-up periods.